2024
DOI: 10.3390/jpm14010094
|View full text |Cite
|
Sign up to set email alerts
|

DeepBiomarker2: Prediction of Alcohol and Substance Use Disorder Risk in Post-Traumatic Stress Disorder Patients Using Electronic Medical Records and Multiple Social Determinants of Health

Oshin Miranda,
Peihao Fan,
Xiguang Qi
et al.

Abstract: Prediction of high-risk events amongst patients with mental disorders is critical for personalized interventions. We developed DeepBiomarker2 by leveraging deep learning and natural language processing to analyze lab tests, medication use, diagnosis, social determinants of health (SDoH) parameters, and psychotherapy for outcome prediction. To increase the model’s interpretability, we further refined our contribution analysis to identify key features by scaling with a factor from a reference feature. We applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 111 publications
0
1
0
Order By: Relevance
“…Employing a two-stage virtual twins model (random forest + decision tree), the research identified factors influencing completion probability (e.g., race/ethnicity, income source), revealing that those without co-occurring mental health conditions, with job-related income, and white non-Hispanics are more likely to complete treatment. Miranda, et al [12] employed deep learning and natural language processing to develop DeepBiomarker2 that accurately predicts alcohol and substance use disorder risk in post-traumatic stress disorder patients and identifies medications and social determinants of health parameters that may reduce this risk. Adams, et al [13] performed a study in Denmark that focused on individuals with substance use disorders (SUDs) and their elevated suicide risk.…”
Section: Introductionmentioning
confidence: 99%
“…Employing a two-stage virtual twins model (random forest + decision tree), the research identified factors influencing completion probability (e.g., race/ethnicity, income source), revealing that those without co-occurring mental health conditions, with job-related income, and white non-Hispanics are more likely to complete treatment. Miranda, et al [12] employed deep learning and natural language processing to develop DeepBiomarker2 that accurately predicts alcohol and substance use disorder risk in post-traumatic stress disorder patients and identifies medications and social determinants of health parameters that may reduce this risk. Adams, et al [13] performed a study in Denmark that focused on individuals with substance use disorders (SUDs) and their elevated suicide risk.…”
Section: Introductionmentioning
confidence: 99%